Sustainable Human Resource Management: a Bibliometric Overview - Putri, Indriana Rezkia (International Journal of Multidisciplinary Sciences, 2023)
The scope of human resource management still being one of the important topics to be studied. The diversity of existing studies required research data that has not been studied much such as sustainable human resource management. The aim of this study is to explore sustainable human resource management research trends over the past 13 years.  The method used to explore research trends is literature review through bibliometric analysis.  The results of bibliometric analysis identify the core study or author, as well as its relationships, by covering all related publications or specific fields. Publications related to sustainable human resource management from 2010-2022 are taken from international journals indexed by Scopus. Sustainable human resource management research trends visualized using vosviewer to analize co-authorship and co-occurrence. The results show the trend of sustainable human resource management research is still not widely carried out, it will become a novelty in human resource management.